Estudo de metarhizium anisopliae (metsch) sorok: toxicidade a compostos extraídos de tibraca limbativentris stal (heteroptera: pentatomidae), efeitos de agroquímicos utilizados na cultura do arroz e aumento da patogenicidade a T. limbativentris com doses subletais de inseticidas químicos - Silva , Rodrigo Alves da (2012)
This study was divided in chapters that include various aspects of the interaction between the entomopathogenic fungus M. anisopliae with rice stink bug T. limbativentris as follows: Chapter 1 (Theoretical considerations) describes an introduction about the elements involved in this study as: the importance of rice crops for Brazil, as well as socio-economic and planted areas with this crop. It also covers information about life cycle and ecology of the rice stink bug, Tibraca limbativentris stal (1869) along with its importance as a pest. Chemical and biological control measures are discussed as well. Regarding the entomopathogenic fungus Metarhizium anisopliae (Metsch.) Sorokin, general aspects of taxonomy, morphology, infection process of this fungus to their hosts and virulence factors were also addressed. To sum up, chemical ecology was explored addressing intraspecific and interspecific interactions among insect family pentatomidae with emphasis on studies of chemical compounds of defense in order to understand the natural resistance of this group of insects to entomopathogenic fungi. Chapter 2 (Toxicity of compounds extracted from the cuticle and the stink methatoracic gland (MTG) of T. limbativentris to the fungus M. anisopliae) describes the susceptibility of different life stages of T. limbativentris to M. anisopliae and correlates these results with the fungicidal activity of aldehydes (E)-2-octenal and (E)-2-dedecenal extracted from metathoracic scent glands (MTG) of adults as well as the (E)-2-hexenal, extracted from dorsal abdominal scent glands (DAG) of nymphal stages (second to fifth instar), by collecting exuviae. All compounds extracted were characterized by GC-MS and their fungistatic potential determined measuring the minimum inhibitory concentration (MIC) of these compounds, which expresses the ability of these compounds to inhibit the conidial germination of this fungus entirely. The aldehyde (E)-2-decenal was the most harmful to M. anisopliae germination, with MIC of 0.003% (30 ppm) compared to the (E)-2-hexenal and (E)-2-octenal, which in turn showed MIC of 0.012 and 0.025%, respectively. Chapter 3 (Effect of pesticides used in conventional rice cultivation with the entomopathogenic fungus M. anisopliae.) Describes the assessment of the compatibility of M. anisopliae to eight insecticides, five herbicides and four fungicides registered for rice cultivation. In this study we evaluated the germination (GER), vegetative growth (VG) and sporulation (ESP) of the fungus after three hours in the mixture, stirring with agrochemicals. The parameters evaluated were the fungus equated using the following formula: BI = [(VG * 47) + (ESP * 43) + (10 * GER)] / 100, in which through the biological index value (BI) was possible to determine the compatibility level of agrochemicals to the fungus. Among the tested pesticides, insecticides Bravic™, Actara™, Karate Zeon™; herbicide Roundup™, Basagran™, Kifix™ and fungicide Priori ™ were the only products compatible with M. anisopliae. Chapter 4 (enhanced pathogenicity toT. limbativentris with sublethal doses of chemical insecticides.) describes the interaction of M. anisopliae combined with sublethal concentrations of thiamethoxam against adults of T. limbativentris. This combination as hypothesis has to overcome the natural chemical resistance of T. limbativentris to M. anisopliae. The results showed that T. limbativentris was more susceptible to M. anisopliae (strain CG-168) associated with sublethal doses of thiamethoxam (Actara™) or lambda-cyhalothrin (Karate Zeon™) than the fungus alone. In addition, the optimum concentration was observed for the fungus at 5x107 conidia combined with concentrations of the insecticide thiamethoxam. The fungus in xxi this concentration mixed with thiamethoxam at 3.1 ppm caused 80% adult mortality, whereas the mortality rates in treatments with the fungus and 3.1 ppm thiamethoxam both applied alone were 38 and 35% respectively. Sublethal doses of Actara™ (3.1 ppm) and Karate Zeon™ (186 ppm) was estimated by Probit equation. For the purpose of using a commercial strain of M. anisopliae, the virulence of strain CG-168, used in all previous tests, was compared to strain 1037-ESALQ, registered commercially. According to the results both strains had similar virulence to adult T. limbativentris. commercially registered in Brazil market. According to the results, adults of T. Limbativentris were similarly susceptible to both strains of M. anisopliae. In the field experiment, five treatments were prepared: Fungus + Actara™ sublethal dose (50g ha), Fungus, Actara™ sublethal dose (50g./ha) Actara™ full dose (200g./ha) and control; which were applied on rice plants infested with insects inside nylon cages under field conditions. After seven and 14 days of application, 20 insects were collected from each cage and evaluated in the laboratory. According to the results, the evaluation of the first collection, mixture of M. anisopliae with 50g/ha Actara™ caused 54% mortality compared with 40, 32, 26 and 18% respectively for the full dose of Actara™ (200g/ha), fungus alone, Actara™ sublethal dose (50g/ha) and control. In the second collection, fungus + Actara™ highlightedin relation to the others, causing a 50% mortality, while treatment with the fungus alone the mortality was16% and the others treatment was 0% As a result, we found a synergism effect between fungus and sublethal dose of the insecticide. In summary, our results highlight the potential of sublethal concentrations of the neonicotinoid insecticide thiamethoxan in increasing the susceptibility of adults of T. Limbativentris to the fungus M. anisopliae. In fact, this strategy consists in a control method effective and feasible to combat this stink rice bug in the field from a viewpoint of an integrated pest management and sustainability.